Spatial variation of vegetation changes in Sokoto region from 2000 to 2018 - Abdullahi ,Muktar; Wali, Elekwachi; Sadiq ,A Yelwa (World Journal of Advanced Research and Reviews, 2022)
Previous researchers reported that vegetation is one of the natural resources that are constantly changing. These changes are mostly found in an area affected by human activities. Those researchers study vegetation using holistic approach without identifying the locations affected and species of plant that withstand the prevailing conditions. The aim of this research was to find out the locations where these changes are mostly affected. This was achieved using Coefficient of Variation analysis on MODIS-EVI dataset, supported by the field observation. The result shows that high CV areas are mostly around farmlands and around the nomadic routes, while low CV areas are around the floodplains of Rivers Sokoto and Rima. The identified plant species that can survive in the high CV areas are Gueira senegalensis (Sabara), Combretum micranthum (Geza) and Piliostigma thonningii (Kalgo). It was recommended that the dominant plant species in the area should be domesticated and used for afforestation programme in the region. Government should provide adequate grazing reserves and animal routes to avoid indiscriminate grazing activities in the area.
Keywords: Vegetation; Coefficient of Variation; Sokoto region; Plant species